Minimally Invasive Oncologic Upper Gastrointestinal Surgery can be Performed Safely on all Weekdays: A Nationwide Cohort Study - Voeten, Daan M. (World J Surg, 2021)
BACKGROUND: Existing literature suggests deteriorating surgical outcome of esophagogastric surgery as the week progresses. However, these studies were conducted in the pre-centralization and pre-minimally invasive era. In addition, they failed to correct for fixed weekdays of esophagogastric cancer surgery among hospitals. This study aimed to describe the impact of weekday of minimally invasive upper gastrointestinal surgery on short-term surgical outcomes. METHODS: All patients registered in the Dutch Upper Gastrointestinal Cancer Audit who underwent curative minimally invasive esophageal or gastric carcinoma surgery in 2015–2019, were included in this nationwide cohort study. Using multilevel multivariable logistic regression, the impact of weekday of surgery on 14 short-term surgical outcomes was investigated. To correct for interhospital variance in fixed weekday(s) of surgery multilevel analyses was used. Results were adjusted for patient, tumor, and treatment characteristics using multivariable logistic regression analyses. RESULTS: This study included 4,102 patients undergoing minimally invasive upper gastrointestinal surgery (2,968 esophageal cancer and 1,134 gastric cancer patients). Weekday of surgery did not impact postoperative complications, severe postoperative complications, surgical/technical complications, medical complications, anastomotic leakage, complicated postoperative course, failure to rescue, surgical radicality, lymph node yield, 30-day/in-hospital mortality, reinterventions, length of ICU stay, 30-day readmission, and textbook outcome after neither esophageal cancer nor gastric cancer surgery. CONCLUSIONS: Minimally invasive esophagogastric surgery can be performed safely on all weekdays with respect to short-term surgical outcomes, which is important information for operation room scheduling. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s00268-021-06160-x.